2018
DOI: 10.7150/ijbs.27774
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 treatment protects endothelial cells from oxidative stress-induced autophagy and endothelial dysfunction

Abstract: Endothelial dysfunction and excessively stimulated autophagy, often caused by oxidant injury or inflammation, will lead to atherosclerosis development and progression in diabetes. The aim of this study is to investigate the protective effect of glucagon-like peptide-1 (GLP-1) treatment on preventing oxidative stress-induced endothelial dysfunction and excessively stimulated autophagy. Treatment of endothelial cells with GLP-1 significantly attenuated oxidative stress-induced endothelial dysfunction and autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 45 publications
2
52
0
Order By: Relevance
“…In this study, we used PA to establish endothelial oxidative stress model to simulate the high saturated fatty acid diet in AS. In the most previous studies of the antioxidant effects of RSV, oxidative stress model is established by H 2 O 2 , which is a type of direct exogenous ROS [4144]. However, although RSV can directly scavenge ROS in vitro, its antioxidant properties in vivo are more likely to be attributed to its effects as a gene regulator [34].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used PA to establish endothelial oxidative stress model to simulate the high saturated fatty acid diet in AS. In the most previous studies of the antioxidant effects of RSV, oxidative stress model is established by H 2 O 2 , which is a type of direct exogenous ROS [4144]. However, although RSV can directly scavenge ROS in vitro, its antioxidant properties in vivo are more likely to be attributed to its effects as a gene regulator [34].…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 has also been shown to have an extra-pancreatic effect that inhibits gastric emptying and reduces food intake [16,17]. GLP-1 receptor agonists have been studied in recent years on cardiovascular disease and endothelial dysfunction [18], and its treatment protects endothelial cells from oxidative stress-induced autophagy and endothelial dysfunction [19]. Liraglutide suppressing endothelin-1 (ET-1) and enhancing endothelium NO synthase (eNOS)/soluble guanylate cyclase (sGC)/protein kinase G (PKG) pathways were also studied in animal models of monocrotaline-induced PAH [20].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that DPP-4 inhibitors decreased oxidative stress and inflammation in the kidney after cisplatin administration in animal models [4,5]. In addition, it has been reported that GLP-1 receptor agonists reduced oxidative stress and inflammation in the kidney in ischemia-reperfusion injury, and protected endothelial cells from oxidative stress-induced injury [32,33].…”
Section: Discussionmentioning
confidence: 94%